Entrepreneurial orientation and family-owned SMEs development: way forward to ‘JAPA’ syndrome in Nigeria - Akeem Olanrewaju Ajani; Noah Senu Padonu; Olaseni A Tairu; Abiodun Thomas Awoyemi (Менеджмент та підприємництво: тренди розвитку, 2025)
Enhancing the functionality of a nation’s economy in the current globalization era requires a dynamic and adaptable entrepreneurial orientation attitude and mindset that can spur innovative ideas, business spirit, and ensure sustain operations in a volatile environment. In this study, seven distinct business sectors - agriculture, construction, schools, real estate, manufacturing, finance and health, in Lagos State, Nigeria, were surveyed cross- sectional to examine entrepreneurial orientation and the development of selected family-owned SMEs: way forward to JAPA syndrome. Two parts of the questionnaire -biographical information and research questions are used to collect data. On the other hand, 217 respondents made up the sample size proportionately, with 31 participants chosen from each study focus. Data analysis was conducted using Pearson correlation statistical tool. According to the study, pro-activeness has a weak but positive correlation with SMEs development. In contrast, the development of family-owned businesses is greatly impacted by innovativeness and autonomy. To end the JAPA syndrome and translate it into economic strengths and opportunities, the government should intensify and vigorously encourage entrepreneurial orientation practices by providing good infrastructure amenities that can increase the development of SMEs and addressing emerging obstacles such as low productivity, unemployment, and insecurity caused by idleness, which stem from the threatening volatile environment. It is recommended that, Proactive measures be used to advance the development and survival of SMEs, and innovation should be pursued as a guiding principle for capacity and adaptability to manage the complexity of the environment. Additionally, business autonomy is considered a necessary component of success, and dynamic orientation should be incorporated to achieve organizational growth and development.